2018
DOI: 10.1186/s12879-018-3113-x
|View full text |Cite
|
Sign up to set email alerts
|

High mortality in patients with Mycobacterium avium complex lung disease: a systematic review

Abstract: BackgroundThe incidence of nontuberculous mycobacterial (NTM) pulmonary disease caused by Mycobacterium avium complex (MAC) in apparently immune-competent people is increasing worldwide. We performed a systematic review of the published literature on five-year all-cause mortality in patients with MAC lung disease, and pooled the mortality rates to give an overall estimate of five-year mortality from these studies.MethodsWe systematically reviewed the literature up to 1st August 2017 using PubMed® and ProQuest … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
97
4

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(107 citation statements)
references
References 30 publications
6
97
4
Order By: Relevance
“…Studies exploring the impact of NTM-LD on mortality have recently been published, showing that NTM-LD is associated with an increased risk of death irrespective of other comorbidities. [16][17][18] Previous studies showed that patients with specific NTM-LD manifestations like cavitary disease 19 or specific NTM species like Mycobacterium xenopi 20 have a higher mortality risk. Specific NTM-LD registries may provide further evidence on the respective risk factors in the future.…”
Section: Management Of Patients With Bronchiectasismentioning
confidence: 99%
“…Studies exploring the impact of NTM-LD on mortality have recently been published, showing that NTM-LD is associated with an increased risk of death irrespective of other comorbidities. [16][17][18] Previous studies showed that patients with specific NTM-LD manifestations like cavitary disease 19 or specific NTM species like Mycobacterium xenopi 20 have a higher mortality risk. Specific NTM-LD registries may provide further evidence on the respective risk factors in the future.…”
Section: Management Of Patients With Bronchiectasismentioning
confidence: 99%
“…Clinical symptoms of NTM lung disease vary in intensity between individuals and are generally non-specific, but they commonly include a chronic cough, sputum production, fatigue and weight loss. Disease progression can lead to deteriorating lung function (often with permanent damage) [ 3 ], reduced physical function and health-related quality of life [ 4 ], together with an increased risk of mortality [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Fourthly, there are alarmingly high death rates in patients following diagnosis with NTM lung infection. A systematic review showed a 5 years mortality showed 27% in Europe, 35% in the US and 33% in Asia (118). Predictors of high mortality included male gender, presence of comorbidities, and fibro cavitary disease.…”
Section: Recent Developments and Research Prioritiesmentioning
confidence: 99%